Meningorradiculomielopatia esquistossomótica Schistosomal meningoradiculomyelopathy: report of two cases - Milberto Scaff; Daniele Riva; A. Spina-França (Arquivos de Neuro-Psiquiatria)
Estudo clínico e laboratorial de dois casos de meningorradiculomielopatia esquistossomótica. Considerações são feitas sobre a fisiopatologia e manifestações neurológicas desta parasitose. A positividade das reações imunológicas para Schistosoma mansoni no líquido cefalorraqueano e as melhoras obtidas mediante terapêutica adequada foram valorizadas para o diagnóstico. The clinical and laboratory findings in two cases of shistosomal meningoradiculomyelopathy due to Schistosoma mansoni are reported. In case 1 the onset and the evolution of the disease assumed a progressive character; the neurologic examination showed a picture similar to the Brown-Sequard syndrome. In case 2 the onset was acute and the neurologic examination has shown a complete transverse myelopathy syndrome at the middle toracic level. The cerebrospinal fluid examination showed in the two cases: cells counts increased, normal or low sugar and increased protein. The study of CSF protein profile showed increased gamma-globulin in the two cases. The immunological reactions in the blood and CSF were positive in the two cases. Good results were obtained with especific therapy.